Nephews as Subjects of Inheritance: Theoretical and Practical Aspects - S. A. Maliar; L. V. Gryshchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on the problems of legal succession by a special category of lawful heirs – nephews. The analysis of scientific works, the authors of which studied specific features of legal succession, has been carried out. All stages of legal succession in accordance with the Civil Code of Ukraine have been listed. The current legislation, court decisions, legal doctrine have been analyzed; and it has been established that inheritance by nephews has problems in practical application.